(untitled) (Revista Española de Derecho Internacional, 2009)
The Spanish Civil War ended 70 years ago. Spanish International Law doctrine stopped going into this conflict in-depth long time ago. The anniversary of the end of the Spanish Civil War, The Historical Memory Law, and references done by the United Nations Human Rights Committee have updated the subject. Besides, the opening of new archives and the devolvement of new researches are showing new juridical and political elements concerning the signification of the Civil War in the development of International Law. This article is limited to clarifying both the law applicable to the Civil War and the contributions dues to the following legal evolution. Spanish Civil War has been relevant for many questions concerning to the principle of non intervention. But this was not the only important question for International Law. The prohibition of the use of force, Human Rights Protection, international humanitarian laee and Diplomatic Asylum were also involved. Some unknown aspects of the Civil War have contributed to the evolution of International Law. The conflict has also been important for other subjects, which demands new researchs and reflections.